2010
DOI: 10.1242/jeb.041889
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of gas exchange pattern and water loss in Scarabaeus spretus (Coleoptera: Scarabaeidae): deconstructing the basis for metabolic rate variation

Abstract: SUMMARYInvestigation of gas exchange patterns and modulation of metabolism provide insight into metabolic control systems and evolution in diverse terrestrial environments. Variation in metabolic rate in response to environmental conditions has been explained largely in the context of two contrasting hypotheses, namely metabolic depression in response to stressful or resource-(e.g. water) limited conditions, or elevation of metabolism at low temperatures to sustain life in extreme conditions. To deconstruct th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 86 publications
3
62
0
Order By: Relevance
“…The control of cuticle permeability is also one of the main mechanisms used to prevent water loss in terrestrial insects and has been shown to be a phenotypically plastic trait (e.g. Stinziano et al, 2015;Terblanche et al, 2010), although its role in aquatic insects has been less well explored (e.g. Alarie et al, 1998;Jacob and Hanssen, 1986).…”
Section: Physiological Mechanisms Linking Tolerance To Salinity and Dmentioning
confidence: 99%
“…The control of cuticle permeability is also one of the main mechanisms used to prevent water loss in terrestrial insects and has been shown to be a phenotypically plastic trait (e.g. Stinziano et al, 2015;Terblanche et al, 2010), although its role in aquatic insects has been less well explored (e.g. Alarie et al, 1998;Jacob and Hanssen, 1986).…”
Section: Physiological Mechanisms Linking Tolerance To Salinity and Dmentioning
confidence: 99%
“…Most insects that remain active in desiccating environments do so by retaining water more effectively through a reduction in the rate of water loss (Gibbs and Matzkin, 2001). This is achieved through a combination of limiting excretory water losses through the mouthparts or anus (Bursell, 1960), by regulating diuresis by decreasing Malpighian tubule activity and/or increasing resorption in the hind-gut (Park, 2012), through reducing respiratory water loss (RWL) via changes in respiratory patterns (Chown et al, 2006;Marais et al, 2005;Terblanche et al, 2010) and through decreasing cuticular water loss (CWL) by reducing cuticular permeability (Chown and Nicolson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Schimpf et al, 2009;Williams et al, 2010) or metabolic rate modulation (e.g. Terblanche et al, 2010), particularly under xeric conditions (e.g. Gefen, 2011), and may therefore be linked to evolutionary fitness (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Schimpf et al, 2012). Manipulation of environmental conditions (such as temperature, moisture or oxygen availability) or the insect's state (rest versus active, dehydrated versus hydrated) can have a dramatic influence on the pattern and overall flux rates exhibited (see Lighton and Turner, 2008;Schimpf et al, 2009;Terblanche et al, 2008;Terblanche et al, 2010;Williams et al, 2010;Matthews and White, 2011a;Matthews and White, 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation